2011
DOI: 10.29309/tpmj/2011.18.02.2047
|View full text |Cite
|
Sign up to set email alerts
|

Breast Feeding

Abstract: Introduction: Breast feeding provides complete and balanced nutrition to the baby. The survey done in 1995 by health ministry, Pakistan reported that although 94 % of the children were ever breastfed, only less than 16 % of the children were exclusively breastfed. Objective: To assess the knowledge, attitude and practices regarding breastfeeding among undergraduate students of medical colleges of Karachi. Materials and Methods: Data Source: Female medical students from Clinical and preclinical years. Study Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…This is in accordance with the knowledge expressed in a study conducted among medical students in Pakistan [10]. Another study conducted among female medical students in Pakistan, found educational level strongly related to the perception regarding initiation and duration of breastfeeding [11]. We also investigated the awareness of the future medical professionals regarding the advantages of breastfeeding; about half of students knew that breastfeeding reduces the rate of subsequent pregnancy and this was in agreement with studies conducted in Pakistan [10,12].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in accordance with the knowledge expressed in a study conducted among medical students in Pakistan [10]. Another study conducted among female medical students in Pakistan, found educational level strongly related to the perception regarding initiation and duration of breastfeeding [11]. We also investigated the awareness of the future medical professionals regarding the advantages of breastfeeding; about half of students knew that breastfeeding reduces the rate of subsequent pregnancy and this was in agreement with studies conducted in Pakistan [10,12].…”
Section: Discussionsupporting
confidence: 91%
“…Also, majority of the medical students in Ziauddin University, Karachi [10] were aware of the advantages of breastfeeding. Almost all the student's opinion was that breast milk can protect the children from common infections [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation